2008
DOI: 10.1007/s00198-008-0808-7
|View full text |Cite
|
Sign up to set email alerts
|

Tibial or hip BMD predict clinical fracture risk equally well: results from a prospective study in 700 elderly Swiss women

Abstract: Summary In a randomly selected cohort of Swiss communitydwelling elderly women prospectively followed up for 2.8± 0.6 years, clinical fractures were assessed twice yearly. Bone mineral density (BMD) measured at tibial diaphysis (T-DIA) and tibial epiphysis (T-EPI) using dual-energy X-ray absorptiometry (DXA) was shown to be a valid alternative to lumbar spine or hip BMD in predicting fractures. Introduction A study was carried out to determine whether BMD measurement at the distal tibia sites of T-EPI and T-DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Whereas the tibial epiphysis (T-EPI) consists predominantly of trabecular bone, the tibial diaphysis (T-DIA) is predominantly composed of cortical bone. The authors previously showed that, in a cohort of randomly selected postmenopausal women, aBMD measured by DXA at both tibial subregions was predictive for non-vertebral fracture risk [17]. T-scores were generally higher at the T-DIA than at the T-EPI suggesting that the T-DIA might be suitable for identifying other contributors of an individual’s fracture risk, including parameters related to the shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the tibial epiphysis (T-EPI) consists predominantly of trabecular bone, the tibial diaphysis (T-DIA) is predominantly composed of cortical bone. The authors previously showed that, in a cohort of randomly selected postmenopausal women, aBMD measured by DXA at both tibial subregions was predictive for non-vertebral fracture risk [17]. T-scores were generally higher at the T-DIA than at the T-EPI suggesting that the T-DIA might be suitable for identifying other contributors of an individual’s fracture risk, including parameters related to the shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…The T ‐scores were calculated as the number of standard deviations from the mean peak bone mass of a female reference population of 400 healthy Caucasians living in the area of Bern, Switzerland. Peak bone mass (mean value ± SD ) of this female reference population is 1.278 ± 0.116 g/cm 2 at the distal tibial diaphysis (Popp et al, 2009).…”
Section: Methodsmentioning
confidence: 94%
“…The manufacturer's software was used according to a previously described standardized procedure for analysing the tibial diaphysis (Casez et al, 1994). Briefly, the region of interest (ROI) for the tibial diaphysis started 130 mm from the distal tibia endplate and included a total length of 40 mm of the long bone axis running from proximal to distal (Figure 1a; Popp et al, 2009). The T ‐scores were calculated as the number of standard deviations from the mean peak bone mass of a female reference population of 400 healthy Caucasians living in the area of Bern, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…If TRP was > 86%, then the formula: TmP/GFR (mmol/l) = (0. Hologic, Bedford, MA, USA) at the lumbar spine, the non-dominant femoral neck, the proximal femur and the distal tibia diaphysis and epiphysis as described [21,22].…”
Section: Study Population and Protocolmentioning
confidence: 99%